Peripheral retinal lesions in highly myopic children: prevalence, types and biometric correlates - Bijon, Jacques; Brach, Louise; Boulanger, Etienne; Chehaibou, Ismael; Couturier, Aude; Panda-Jonas, Songhomitra; Abdelmassih, Youssef; Bonnin, Sophie; Caputo, Georges; Chapron, Thibaut (British journal of ophthalmology, 2025)
Aims: To evaluate prevalence, types and biometric predictors of peripheral retinal lesions in highly myopic children. - Methods: Retrospective cross-sectional study at a tertiary centre. Participants were aged 4-17 years with high myopia (≤−4.00 dioptres (D) at 4-6 years; ≤−6.00 D at 7-17 years). Peripheral retina was assessed by ultra-widefield imaging (UWF) and/or documented dilated ophthalmoscopy. - Results: We analysed 160 eyes from 89 children (mean age 10.4±3.8 years; mean spherical equivalent −9.95±3.59 D; mean axial length (AL) 26.68±1.82 mm). Peripheral lesions were present in 87/160 eyes (54.4%), more frequent in 7-17-year-olds than in 4-6-year-olds (59.4% vs 34.4%) (p<0.05). Among affected eyes, 50/87 (57%) had a single lesion and 37/87 (43%) multiple; multiplicity increased with age (p<0.001). The most frequent lesions were dark without pressure (46/160; 28.7%), white without pressure (32/160; 20.0%), snail-track degeneration (15/160; 9.4%), microcystoid degeneration (11/160; 6.9%) and lattice degeneration (10/160; 6.3%). In multivariate models, AL was the strongest independent predictor of both lesion prevalence (OR=1.45; 95% CI 1.07 to 2.03; p=0.021) and multiplicity (OR=2.17; 95% CI 1.53 to 3.07; p<0.001). Model-derived lesion probability reached 50% at AL 26.2 mm and 80% at 29.4 mm. - Conclusions: Peripheral retinal lesions are common in paediatric high myopia and related strongly to AL. Early peripheral retinal assessment using UWF imaging or thorough dilated examination may enhance risk stratification and surveillance.
Vorab online veröffentlicht: 07. Dezember 2025
Gesehen am 09.02.2026